Effect of cooking temperature on metal concentrations and speciation in fish muscle and seal liver - Marc Amyot; Emma Husser; Kathy St-Fort; Dominic E. Ponton (Ecotoxicology and Environmental Safety, 2023)
Fish and marine mammals constitute a significant part of the country food diet of many Indigenous communities in Canada. These animals sometimes accumulate essential elements as well as elevated levels of toxic metals. We experimentally assessed how changes in cooking temperature (23–99 °C by boiling) modified elemental concentrations in whitefish muscle and grey seal liver (two organs commonly consumed in some northern communities). Wet and dry elemental concentrations changed linearly as a function of temperature, and two patterns were observed: methylmercury, selenium, and rare earth elements tended to remain associated with the food during cooking, whereas alkali, alkaline-earth metals, and arsenic were significantly transferred to cooking juices. Mass balances indicated that speciation of mercury was stable during cooking. Because elements generally behaved similarly as those of their periodic table group or their ecotoxicological classes (A, B, intermediate), we propose that elemental behavior during cooking is partly a function of chemical affinity, and this relationship can be used to predict the behavior of data-poor elements of emerging concern, such as technology-critical elements. Furthermore, the marked increases and decreases in elemental concentrations during cooking (e.g., −14% As and +39% Se in whitefish; −22% Cd and +55% Hg in seal liver, on a wet weight basis) should be considered when assessing risk because current exposure models usually only consider elemental concentrations in raw food.